Trimble Acquires Gehry Technologies. - beaman, michael leighton (Architectural Record, 2014)
The article reports that technology company Trimble Navigation Limited acquired architecture, engineering, and construction (AEC) technology company Gehry Technologies (GT). Topics discussed include other acquisitions made by Trimble, the level of software development that will occur at GT following the acquisition, and the cloud-based project management platform by GT that was part of the acquisition.